Malaysia pharmacy students' assessment of an objective structured clinical examination (OSCE) - Awaisu, Ahmed; Ab Rahman, Norny Shafinaz; Nik Mohamed, Mohamad Haniki; Shaikh Rahman Bux, Siti Halimah Bux; Mohamed Nazar, Nor Ilyani (American Association of Colleges of Pharmacy (AACP), 2010)
Objective To implement and determine the effectiveness of an objective structured clinical examination (OSCE) to assess fourth-year pharmacy students' skills in a clinical pharmacy course.